THE RELATIONSHIP BETWEEN FREQUENCY OF BREASTFEEDING AND NEWBORN WEIGHT LOSS - Ratna Ariesta Dwi Andriani; Uliyatul Laili (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Harapan Bersama, 2021)
Breast milk contains many nutrients, an ideal composition for the baby's needs in the growth stage. In the first ten days, the newborn's weight will decrease by less than 10% of birth weight. Adequacy of breastfeeding for newborns can increase the baby's weight significantly. Mostly, weight is used to determine the baby's growth. To increase the baby's weight, the baby needs proper nutrition, and breastmilk is the primary nutrition for babies less than six months old. One of the factors that influence breast milk production is the frequency of breastfeeding. It helps to stimulate breast milk production. This research aims to analyze the relationship between the frequency of breastfeeding and newborn weight loss. This research used purposive sampling, and the collected data were analyzed using chi-square. The analysis showed that the p-value is 0.003, which means a significant relationship between breastfeeding frequency and newborn weight loss. Keywords: Frequency of breastfeeding, Baby weight